Answer:
![x+2y-7=0](https://img.qammunity.org/2020/formulas/mathematics/college/ts9t876b0der7twceb00ymbj45svg1zhlu.png)
Explanation:
We know that the equation of a line passing through points (a,b) and (c,d) is given by :-
![(y-b)=(d-b)/(c-a)(x-a)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/70alc0d535v7uc2mkbzf69hygd9rrmf3lk.png)
Then , the equation of a line passing through points (3,2) and (1,3) is given by :-
![(y-2)=(3-2)/(1-3)(x-3)\\\\\Rightarrow\ (y-2)=(1)/(-2)(x-3)\\\\\Rightarrow\ -2(y-2)=(x-3)\\\\\Rightarrow\ -2y+4=x-3\\\\\Rightarrow\ x+2y-7=0](https://img.qammunity.org/2020/formulas/mathematics/college/i5h6sckg8s7l5drhclzv53js18fn3sq0hb.png)
Hence, the equation of a line passing through points (3,2) and (1,3) is :
![x+2y-7=0](https://img.qammunity.org/2020/formulas/mathematics/college/ts9t876b0der7twceb00ymbj45svg1zhlu.png)